Pengaruh Komitmen Profesional Terhadap Whistleblowing Intention: Locus Of Control Sebagai Variabel Moderating : Studi Persepsi Mahasiswa Akuntansi Universitas Flores - Baptista, Selviana Risska; Banda, Falentina L; Londa, Yulita (Jurnal Riset Ilmu Akuntansi, 2021)
The purpose of this study was to determine the level of influence of professional commitment on whistleblowing intention, with locus of control as the moderating variable. The population in this study were all students in the accounting study program. Based on the purposive sampling method, this study used a sample of 72 respondents and the sample was semester VIII, X and XII students with the criteria of having passed the ethics and business profession courses, auditing 1 and 2. The dependent variable (Y) of this study is Whistleblowing intention. The independent variable (X1) is professional commitment and the moderating variable (X2) is locus of control. The method used is quantitative research methods. This study uses primary data, namely a questionnaire. Data were analyzed using simple regression analysis and moderating regression analysis which was managed through IBM SPSS Statistic ver 14 software. The results showed that professional commitment has an effect on Whistleblowing Intention with a significance value of 0.000 less than 0.05. However, locus of control did not moderate the relationship between professional commitment and Whistleblowing Intention with a significance value of 0.163 greater than 0.05.